Comprehensive physical examination for instability of the knee - Lubowitz, J. H.; Bernardini, B. J.; Reid, J. B. (The American Journal of Sports Medicine, 2008)
A careful history and physical examination are the cornerstones of orthopaedic sports medicine. When evaluating a patient for ligamentous instability of the knee joint, an understanding of the contribution of anatomic structures to stability enhances a practitioner`s ability to achieve an accurate clinical diagnosis. This article reviews the various types of knee instability and the associated anatomic structures. Ultimately, information must be obtained from multiple tests to reach the final diagnosis. We describe in detail the pathologic and biomechanical basis of the tests for both tibiofemoral and patellofemoral instability of the knee joint and provide recommendations for performance and interpretation of these physical examinations.